Isolation and Characterization of 22,23-Dihydrostigmasterol (β-Sitosterol) from the Bark of Polyalthia longifolia var. angustifolia - Ghosh, G.; Subudhi, B.B.; Mishra, D.; Sudhir Kumar, P.; Mishra, S.K. (Asian Journal of Chemistry, 2010)
The phytosterol namely 17-(5-ethyl-6-methylhaptane-2-yl)-10,13-dimethyl-2,3,4,7,8,9,11, 12,14,15,16,17-dodecahydro-1H-cyclopenta(phenanthren-3-ol) has been isolated from methanolic extract of bark of Polyalthia longifolia var. angustifolia. The structure of the isolated compound was established on the basis of elemental analysis and spectroscopic evidences of IR, UV-vis, 1H NMR, 13CNMR and EIMS.